Whole genome sequencing reveals within-host genetic changes in paired meningococcal carriage isolates from Ethiopia - Guro K. Bårnes (BMC Genomics, 2017)
Abstract Background Meningococcal colonization is a prerequisite for transmission and disease, but the bacterium only very infrequently causes disease while asymptomatic carriage is common. Carriage is highly dynamic, showing a great variety across time and space within and across populations, but also within individuals. The understanding of genetic changes in the meningococcus during carriage, when the bacteria resides in its natural niche, is important for understanding not only the carriage state, but the dynamics of the entire meningococcal population. Results Paired meningococcal isolates, obtained from 50 asymptomatic carriers about 2 months apart were analyzed with whole genome sequencing (WGS). Phylogenetic analysis revealed that most paired isolates from the same individual were closely related, and the average and median number of allelic differences between paired isolates defined as the same strain was 35. About twice as many differences were seen between isolates from different individuals within the same sequence type (ST). In 8%, different strains were detected at different time points. A difference in ST was observed in 6%, including an individual who was found to carry three different STs over the course of 9 weeks. One individual carried different strains from the same ST. In total, 566 of 1605 cgMLST genes had undergone within-host genetic changes in one or more pairs. The most frequently changed cgMLST gene was relA that was changed in 47% of pairs. Across the whole genome, pilE, differed mostly, in 85% of the pairs. The most frequent mechanisms of genetic difference between paired isolates were phase variation and recombination, including gene conversion. Different STs showed variation with regard to which genes that were most frequently changed, mostly due to absence/presence of phase variation. Conclusions This study revealed within-host genetic differences in meningococcal isolates during short-term asymptomatic carriage. The most frequently changed genes were genes belonging to the pilin family, the restriction/modification system, opacity proteins and genes involved in glycosylation. Higher resolution genome-wide sequence typing is necessary to resolve the diversity of isolates and reveals genetic differences not discovered by traditional typing schemes, and would be the preferred choice of technology.